Lectura hermenéutica. Bolívar y Miranda, vidas cruzadas para una interpretación histórica y literaria. / Hermeneutical Reading. Bolívar and Miranda, Crossed Lives for a Historical and Literary Interpretation. - LEÓN GONZÁLEZ, Libertad (Utopía y Praxis Latinoamericana, 1970)
RESUMEN La novela histórica indefectiblemente se nutre de la tradición y la historia. Revisar la vida de Simón Bolívar (1783-1830) y Francisco de Miranda (1750-1816) desde la novela histórica es una invitación expresa a revisar textos que retomen la vida de ambos hombres ilustres. La biografía posee esa expresa información sobre los grandes momentos acaecidos en cada personaje histórico, hasta el punto de reconocerse en sus líneas una exaltación, muchas veces, también idealizada de sus vidas. Acercarse a este género ofrece sugerentes aspectos de interpretación de la hermenéutica iberoamericana sobre esos seres recreados de la ficción novelesca.ABSTRACT The historical novel, with no doubt, is nourished by the tradition and history. Reviewing the lives of Simon Bolivar (1783-1830) and Francisco de Miranda (1750-1816) from the historical novel is an express invitation to study again those texts that return to the lives of both illustrious men. The biography has that express information about the great moments lived by each historical character to the point of recognizing in their lines an exaltation, idealistic in many times, of their lives. Approaching this genre offers suggestive aspects of interpretation of Ibero-American hermeneutics about those creatures recreated in the novel fiction.